Securing the Future: How Organizations Can Combat AI-Based Attacks - Nazanin Sadat Hashemian, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
Artificial Intelligence (AI) in the field of cybersecurity is recognized as a double-edged sword; on one hand, it strengthens cyber defense, while on the other, cyber attackers also exploit it to create more sophisticated attacks (1). AI tools are highly effective for rapid data analysis and threat pattern recognition, which helps organizations prevent cyberattacks. For example, AI can identify attacks in real-time and prevent their progression—something that is challenging with traditional methods (2). However, hackers also use AI to design complex and deceptive attacks, bypassing security systems using advanced algorithms (3).